Intraoperative ultrasound imaging in the surgical treatment of congenital hyperinsulinism: prospective, blinded study. Issue 2 (11th November 2020) - Bjarnesen, A P; Dahlin, P; Globa, E; Petersen, H; Brusgaard, K; Rasmussen, L; Melikian, M; Detlefsen, S; Christesen, H T; Mortensen, M B
Abstract: Background: In congenital hyperinsulinism (CHI), preoperative prediction of the histological subtype (focal, diffuse, or atypical) relies on genetics and 6-[ 18 F]fluoro-l -3, 4-dihydroxyphenylalanine ( 18 F-DOPA) PET–CT. The scan also guides the localization of a potential focal lesion along with perioperative frozen sections. Intraoperative decision-making is still challenging. This study aimed to describe the characteristics and potential clinical impact of intraoperative ultrasound imaging (IOUS) during CHI surgery. Methods: This was a prospective, observational study undertaken at an expert centre over a 2-year interval. IOUS was performed blinded to preoperative diagnostic test results (genetics and 18 F-DOPA PET–CT), followed by unblinding and continued IOUS during pancreatic resection. Characteristics and clinical impact were assessed using predefined criteria. Results: Eighteen consecutive, surgically treated patients with CHI, with a median age of 5.5 months, were included (focal 12, diffuse 3, atypical 3). Focal lesions presented as predominantly hypoechoic, oval lesions with demarcated or blurred margins. Patients with diffuse and atypical disease had varying echogenicity featuring stranding and non-shadowing hyperechoic foci in three of six, whereas these characteristics were absent from those with focal lesions. The blinded IOUS-based subclassification was correct in 17 of 18 patients; one diffuse lesion was misclassified as focal. IOUS had an impact on the surgical approach in most patients with focal lesions (9 of 12), and in those with diffuse (2 of 3) and atypical (2 of 3) disease when the resection site was close to the bile or pancreatic duct. Conclusion: Uniform IOUS characteristics made all focal lesions identifiable. IOUS had a clinical impact in 13 of 18 patients by being a useful real-time supplementary modality in terms of localizing focal lesions, reducing the need for frozen sections, and preserving healthy tissue and delicate structures. Abstract : Intraoperative decision-making in surgical treatment of congenital hyperinsulinism is challenging. At our institution we use intraoperative ultrasound to comply with these challenges. This study presents prospective and blinded data on intraoperative ultrasound characteristics and its impact on the surgical approach.